Strategi Guru Mengenalkan Konsep Sains Dan Matematika Dengan Media Teknologi di TKAdni Surabaya - Mei Ariani Kusumawati; Ruqoyyah Fitri (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Project-based science learning with MELESAT content using loose parts is the choice as a learning model for young children to build new knowledge, with a scientific mindset children are getting to know Al-Khaliq, exploring new things, being creative, innovative, thinking out of the box, are adaptive to the environment, able to produce work and can develop and practice skills related to the real world. One way to learn science more constructively and meaningfully is through project-based learning that integrates MELESAT components using loose parts as open-ended play materials. Through continuous particSainstion in various play activities in the classroom and outside the classroom, children are actively involved in dialogue that is rich in scientific thinking patterns by utilizing complex and abstract scientific process skills such as observing, asking, observing, predicting, evaluating, and comparing. Discussions with children during the learning process about scientific thinking concepts related to mathematics, existence, literacy, engineering, science, art and technology merge with strengthening coaching by teachers for children during the learning process. The results of this research led to the conclusion that with the right teacher guidance, the learning process provides many opportunities for children to develop 21st century skills to prepare children for life in the future.